2017
DOI: 10.1111/1759-7714.12404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐term outcomes and three yearsurvival between total minimally invasiveMcKeown and dual‐incision esophagectomy

Abstract: BackgroundThe aim of this study was to compare the short‐term outcomes and three‐year survival between dual‐incision esophagectomy (DIE) and total minimally invasive McKeown esophagectomy (MIME) for esophageal cancer patients with negative upper mediastinal lymph nodes requiring esophagectomy and neck anastomosis.MethodsOne hundred and fifty patients underwent DIE, while 361 patients received total MIME. Perioperative outcomes and three‐year survival were compared in unmatched and propensity score matched data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Nearly 50% of esophageal cancer cases and deaths resulting from esophageal cancer occur in China . Esophageal squamous cell carcinoma (ESCC) accounts for > 90% of all pathological types of esophageal cancer in China . Surgery is the main treatment for resectable esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 50% of esophageal cancer cases and deaths resulting from esophageal cancer occur in China . Esophageal squamous cell carcinoma (ESCC) accounts for > 90% of all pathological types of esophageal cancer in China . Surgery is the main treatment for resectable esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Esophageal squamous cell carcinoma (ESCC) accounts for > 90% of all pathological types of esophageal cancer in China. 3,4 Surgery is the main treatment for resectable esophageal cancer. In recent years, with the development of medical science, surgical methods for treating esophageal cancer have made great progress, but the prognosis of esophageal cancer is still poor.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the range of abdominal lymph node dissection for OSE was significantly lower than that for the abdominal‐transhiatal approach . Meanwhile, an increasing number of studies have reported that the range of lymph node dissection with the laparoscopic approach was comparable to open surgery . The results of this study show that the numbers and locations of dissected lymph nodes were better in the MISE group than those in the OSE group.…”
Section: Discussionmentioning
confidence: 59%
“…Although it was a small study, no difference (43), performed a controlled randomized study comparing the short-term outcomes and 3-year survival between total MIE 3 stage McKeown and the so called dual-incision esophagectomy through an open left thoracotomy (DIE = Sweet procedure). They concluded that MIE and DIE yielded comparable short-term outcomes, however MIE was associated with better three year overall and disease-free survival (43). Moreover, Sun et al (44) performed an important control randomized study comparing two groups of patients operated by MIE 3 stage Mckeown esophagectomy.…”
Section: Minimally Invasive Approachesmentioning
confidence: 99%